The Impact Of Content Marketing On Customer Retention: A Study Of Ncr-rouiba Company - Hassani Abdelakrim; Bouketir Djebar (جامعة الوادي University of Eloued, 2024)
This study investigates the impact of content marketing on customer retention within the context of NCR-Rouiba Company. Building upon existing literature, five key dimensions of content marketing were identified: relevance, credibility, attractiveness, value, and emotional impact. A sample of 267 customers from NCR Rouiba Company participated in the study. Data analysis employed descriptive statistics (frequencies, percentages) and simple linear regression analysis to test the hypotheses. The findings demonstrate a significant positive impact of content marketing on customer retention. Furthermore, all five dimensions of content marketing were found to individually contribute to customer retention.
Keywords: Content Marketing; Dimensions of Content Marketing; Relevance of Content; Customer Retention; NCR-Rouiba Company